2017
DOI: 10.1016/j.jaci.2016.07.036
|View full text |Cite
|
Sign up to set email alerts
|

The nasal methylome and childhood atopic asthma

Abstract: Background Given strong environmental influence on both epigenetic marks and allergic asthma in children, the epigenetic alterations in respiratory epithelia may provide insight into allergic asthma. Objective To identify DNA methylation and gene expression changes associated with childhood allergic persistent asthma. Methods We compared genomic DNA methylation patterns and gene expression in African American children with persistent atopic asthma[N=36] versus healthy controls[N=36]. Results were validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
180
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(195 citation statements)
references
References 70 publications
(95 reference statements)
13
180
0
Order By: Relevance
“…Some of the genes with the most prominent changes in DNA methylation and gene expression are consistent in nasal and airway epithelia (CAPN14, CTSC, and FBXL7, among others), whereas we identified other genes with larger changes in nasal epithelia (POSTN, CCL26, GATA2, HLA genes, to name a few). The majority of the genes with the most pronounced methylation-expression relationships were also identified in our previous nasal epithelial study (5), despite differences in age, ethnicity, and potential exposures between the two cohorts.…”
supporting
confidence: 51%
“…Some of the genes with the most prominent changes in DNA methylation and gene expression are consistent in nasal and airway epithelia (CAPN14, CTSC, and FBXL7, among others), whereas we identified other genes with larger changes in nasal epithelia (POSTN, CCL26, GATA2, HLA genes, to name a few). The majority of the genes with the most pronounced methylation-expression relationships were also identified in our previous nasal epithelial study (5), despite differences in age, ethnicity, and potential exposures between the two cohorts.…”
supporting
confidence: 51%
“…109 The magnitude of the methylation changes observed in nasal epithelia of these asthmatic children approaches that reported in malignancies. 110, 111 60% of genes that are differentially expressed in the asthmatic nasal epithelium have significant associations between DNA methylation and gene expression; these include asthma genes ( ALOX15 , CAPN14 , POSTN ), genes involved in inflammation and immunity, cell adhesion, extracellular matrix, obesity and autophagy, and epigenetic regulators, among others.…”
Section: Asthma Epigeneticsmentioning
confidence: 64%
“…As is evident from our analyses, adjusting for granulocytes alone does not appear to be sufficient for countering the confounding effects of eosinophils in EWAS using whole blood; however, EWAS based on DNA methylation from PBMC samples may be less affected by cell-type differences. Similarly, a study of asthma using methylation data from nasal epithelium observed associations between asthma and DNA methylation but did not specifically adjust for eosinophil cell counts [24]. However, the authors in this study did attempt to perform cell sorting which may have negated some of the confounding effects of cell mixtures by ensuring a more homogenous cell sample enriched for epithelial cells.…”
Section: Comparisons With Previous Literaturementioning
confidence: 97%
“…However, whether these associations are also present for the asthma phenotype has not been assessed. Studies that have examined DNA methylation associations with asthma have not specifically determined whether observed associations are due to cell type confounding between samples [23,24]. Eosinophils, a type of circulating granulocyte, are known to be increased in peripheral blood of some people with allergic conditions, such as certain subtypes of asthma [25,26].…”
Section: Introductionmentioning
confidence: 99%